Internal Risk Rating System Regulatory Compliance and Sustainability of Rural Banks in Laguna - Recoco, Gilbert (International Journal of Sustainability and Advanced Integrated Research, 2026)
This study examined the regulatory compliance of the internal risk rating system of Rural Banks (RBs) in Laguna and its relationship with economic, environmental, and societal sustainability. Anchored on the Sustainable Finance Framework, the Credit Risk Management System under Sections 153 and 143 of the Manual of Regulations for Banks, the Theory of Planned Behavior, and the Triple Bottom Line, the study employed a quantitative descriptive-correlational research design. Data were collected using a validated researcher-made questionnaire administered to 100 bank personnel selected through stratified random sampling from a population of 245 respondents. Statistical analyses included the weighted mean and Pearson product-moment correlation coefficient. The findings revealed that the Rural Banks in Laguna fully complied with the Sustainable Finance Framework and Credit Risk Management System. Likewise, the banks demonstrated highly sustained economic, environmental, and societal sustainability in their credit operations. A significant positive relationship was found between regulatory compliance and environmental sustainability, while no significant relationships were observed with economic and societal sustainability. Based on these findings, an action plan was developed to strengthen the integration of sustainability principles into the internal risk rating system through enhanced risk profiling, policy development, risk monitoring, and validation procedures. The study concludes that strong regulatory compliance supports environmentally sustainable credit operations and recommends continuous monitoring, regular validation of the internal risk rating system, and periodic enhancement of sustainable risk management practices. The study supports Sustainable Development Goal (SDG) 8: Decent Work and Economic Growth, SDG 9: Industry, Innovation and Infrastructure, and SDG 13: Climate Action by promoting responsible lending, sustainable financial management, and the integration of environmental considerations into banking operations. Its findings contribute to institutional, environmental, and economic sustainability by providing evidence that can guide rural banks and regulators in strengthening sustainable credit risk management and long-term financial resilience.
Keywords: Credit Risk Management; Environmental Sustainability; Internal Risk Rating System; Regulatory Compliance; Rural Banks; Sustainable Finance; Sustainability